The Gateway to Computer Science Excellence

+4 votes

The only problem I see is the Left recursion.

Therefore the new grammar would be

$S\rightarrow \left ( L \right )|a$

$L\rightarrow SL'$

$L'\rightarrow .SL' | \epsilon$

$-----------------------------------$

FT( S)={( ,a }

FT( L)={ ( ,a}

FT( L' )={ .,$\epsilon$}

FL( S)={ $,.,( ,a }

FL( L)={ )}

FL( L')={ ) }

Therefore the new grammar would be

$S\rightarrow \left ( L \right )|a$

$L\rightarrow SL'$

$L'\rightarrow .SL' | \epsilon$

$-----------------------------------$

FT( S)={( ,a }

FT( L)={ ( ,a}

FT( L' )={ .,$\epsilon$}

FL( S)={ $,.,( ,a }

FL( L)={ )}

FL( L')={ ) }

- All categories
- General Aptitude 1.9k
- Engineering Mathematics 7.5k
- Digital Logic 2.9k
- Programming and DS 4.9k
- Algorithms 4.4k
- Theory of Computation 6.2k
- Compiler Design 2.1k
- Databases 4.1k
- CO and Architecture 3.4k
- Computer Networks 4.2k
- Non GATE 1.4k
- Others 1.4k
- Admissions 595
- Exam Queries 573
- Tier 1 Placement Questions 23
- Job Queries 72
- Projects 18

50,737 questions

57,370 answers

198,506 comments

105,274 users